Systematic Review of Publications Regarding Quadriceps Tendon Autograft Use in Anterior Cruciate Ligament Reconstruction - Walker M. Heffron, B.S; Jennifer L. Hunnicutt, Ph.D., A.T.C; John W. Xerogeanes, M.D; Shane K. Woolf, M.D; Harris S. Slone, M.D (Elsevier, 2019)
Purpose: To perform a systematic review with quantitative and qualitative analysis of publications to date focusing on the use of quadriceps tendon (QT) autografts in anterior cruciate ligament (ACL) reconstruction and to define the regional variability, type of publication, level of evidence, journal of publication, and type of QT graft used. Methods: The PubMed, Scopus, and Google Scholar databases were systematically queried for journal articles relating to QT autografts used for ACL reconstruction through 2018. These publications were filtered for relevance and then analyzed and differentiated by publication characteristics. Results: Most articles were published in the United States and Europe, and most articles evaluating clinical outcomes were Level of Evidence III. Over 60% of the publications (115 of 187) focusing on QT for ACL reconstruction were published within the past 10 years, and 30% (56 of 187) were published within the past 3 years. The results not only showed a recent increase in the number of publications regarding QT as a choice for the autograft harvest site in ACL reconstruction over time, but also yielded informative data regarding the publication journal, country or region, and level of evidence. Conclusions: This evaluation shows the increasing interest in the scientific evaluation of QT as a source of autograft tissue for ACL reconstruction. Clinical Relevance: Increased production of high-quality research will allow surgeons to feel more confident in their use of the QT as an autograft option in ACL reconstruction.